Perlindungan Hukum bagi Konsumen terhadap Penyalahgunaan Platform Trading Cryptocurrency di Indonesia - Herli Antoni; Lindryani Sjofjan; Eka Ardianto Iskandar; Tatang Tatang (Juris Prima: Jurnal Inovasi Hukum dan Kebijakan, 2026)
The rapid advancement of information technology and economic digitalization has introduced cryptocurrency as a significant innovation in the global financial sector. In Indonesia, cryptocurrencies are increasingly popular as both investment instruments and commodities on various trading platforms. However, the proliferation of cryptocurrency usage presents numerous legal challenges, particularly concerning consumer protection. The inherent characteristics of cryptocurrency transactions—namely being digital, decentralized, and anonymous—create vulnerabilities to abuse by trading platforms, including fraud, market manipulation, and breach of contract. This situation was exacerbated by the absence of specific regulations and weak supervision during the early stages of crypto asset development in Indonesia. This study aims to analyze the existing forms of legal protection for consumers in Indonesian cryptocurrency transactions, identify the factors contributing to trading platform abuses, and evaluate the effectiveness of the Financial Services Authority (OJK) in safeguarding consumers. Utilizing a normative juridical approach supplemented by empirical studies, the research reveals that consumer protection in this sector urgently requires regulatory strengthening, particularly regarding information transparency, dispute resolution mechanisms, and platform supervision. Furthermore, the transition of regulatory and supervisory authority from Bappebti to the OJK and Bank Indonesia in 2025 represents a crucial step toward enhancing legal protection and certainty. The findings of this research are intended to provide valuable insights for the government, OJK, and relevant stakeholders to formulate adaptive policies that effectively protect consumer rights and foster a healthy, sustainable digital financial ecosystem.